2018
DOI: 10.5603/pjnns.a2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

No association between MRI changes in the lumbar spine and intensity of pain, quality of life, depressive and anxiety symptoms in patients with low back pain

Abstract: Introduction. The association between changes in magnetic resonance imaging (MRI) and clinical symptoms in patients with low back pain (LBP) is unclear. Aim. To evaluate correlations between combined MRI findings of the lumbar spine (LS) and pain intensity, depressive and anxiety symptoms and quality of life in patients with LBP. Material and methods. 200 subjects (93 men and 107 women; mean age 51.42 ± 13.21 years) with LBP referred for MRI were enrolled in the study. All patients completed the Hospital Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…6) In contrast to the above findings, there is some evidence that muscle CSA is not associated with pain, disability, or quality of life (QoL) in patients with nonspecific LBP. 7) Furthermore, it has been reported that some degeneration occurs even in people without LBP. 8) For instance, Chung et al suggested that endplates of the intervertebral disc were found in asymptomatic healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…6) In contrast to the above findings, there is some evidence that muscle CSA is not associated with pain, disability, or quality of life (QoL) in patients with nonspecific LBP. 7) Furthermore, it has been reported that some degeneration occurs even in people without LBP. 8) For instance, Chung et al suggested that endplates of the intervertebral disc were found in asymptomatic healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, besides reliability a diagnostic method also requires adequate validity to allow for use in clinical practice. Several trials have shown, that degenerative changes of the lumbar spine do not necessarily correlate with clinical symptoms [26, 27]. Even advanced imaging techniques fail to clearly identify the source of symptoms in patients with low back pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, around 13% of the general population have some form of CKD [ 3 ]. In 2016, around 1.2 million deaths and 35 million disability-adjusted life years were attributed to CKD globally, which represents an increase in mortality and disability by 98 and 62% since 1990, respectively [ 4 ]. A significant proportion of patients with CKD progress to end stage renal disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%